How climate impacts the composition of wolf‐killed elk in northern Yellowstone National Park. Issue 6 (27th March 2020) - Wilmers, Christopher C.; Metz, Matthew C.; Stahler, Daniel R.; Kohl, Michel T.; Geremia, Chris; Smith, Douglas W.
Abstract: While the functional response of predators is commonly measured, recent work has revealed that the age and sex composition of prey killed is often a better predictor of prey population dynamics because the reproductive value of adult females is usually higher than that of males or juveniles. Climate is often an important mediating factor in determining the composition of predator kills, but we currently lack a mechanistic understanding of how the multiple facets of climate interact with prey abundance and demography to influence the composition of predator kills. Over 20 winters, we monitored 17 wolf packs in Yellowstone National Park and recorded the sex, age and nutritional condition of kills of their dominant prey—elk—in both early and late winter periods when elk are in relatively good and relatively poor condition, respectively. Nutritional condition (as indicated by per cent marrow fat) of wolf‐killed elk varied markedly with summer plant productivity, snow water equivalent (SWE) and winter period. Moreover, marrow was poorer for wolf‐killed bulls and especially for calves than it was for cows. Wolf prey composition was influenced by a complex set of climatic and endogenous variables. In early winter, poor plant growth in either year t or t  − 1, or relatively low elk abundance, increased the odds of wolves killing bulls relative to cows. Calves were most likely to get killed when elk abundance was high and when the forage productivity they experienced in utero was poor. In late winter, low SWE and a relatively large elk population increased the odds of wolves killing calves relative to cows, whereas low SWE and poor vegetation productivity 1 year prior together increased the likelihood of wolves killing a bull instead of a cow. Since climate has a strong influence on whether wolves prey on cows (who, depending on their age, are the key reproductive components of the population) or lower reproductive value of calves and bulls, our results suggest that climate can drive wolf predation to be more or less additive from year to year. Abstract : The impacts of large carnivores on their prey are importantly impacted by the composition of the prey killed. Here the authors show that climate and elk population size interact in important ways to determine when wolves kill cows, bulls or calves.